2018
DOI: 10.1002/btpr.2642
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic parameter determination for complex biological feedstocks

Abstract: The application of mechanistic models for chromatography requires accurate model parameters. Especially for complex feedstocks such as a clarified cell harvest, this can still be an obstacle limiting the use of mechanistic models. Another commonly encountered obstacle is a limited amount of sample material and time to determine all needed parameters. Therefore, this study aimed at implementing an approach on a robotic liquid handling system that starts directly with a complex feedstock containing a monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In our hands, purities of >50% are typically required to obtain a Gaussian curve-shaped peak for fitting ( Bernau et al, 2021 ), yet higher purities may be necessary depending on the type, number and individual abundance of non-target protein impurities. The presence of such impurities may result in shoulders or even several peak maxima, which in the simplest case can falsify the fitted transport parameters, and in the worst case can result in incorrect protein-specific isotherm parameters due to the selection of inappropriate peak properties, e.g., maxima, for fitting ( Pirrung et al, 2018 ). Nevertheless, the inverse method can determine parameter values for multicomponent isotherms, even for separation factors of 0.9–1.1 ( Kaczmarski 2007 ; Hahn et al, 2016a ), if the corresponding proteins do not interact with each other.…”
Section: Challenge Ii: Obtaining Experimental Data To Set Up the Modelmentioning
confidence: 99%
“…In our hands, purities of >50% are typically required to obtain a Gaussian curve-shaped peak for fitting ( Bernau et al, 2021 ), yet higher purities may be necessary depending on the type, number and individual abundance of non-target protein impurities. The presence of such impurities may result in shoulders or even several peak maxima, which in the simplest case can falsify the fitted transport parameters, and in the worst case can result in incorrect protein-specific isotherm parameters due to the selection of inappropriate peak properties, e.g., maxima, for fitting ( Pirrung et al, 2018 ). Nevertheless, the inverse method can determine parameter values for multicomponent isotherms, even for separation factors of 0.9–1.1 ( Kaczmarski 2007 ; Hahn et al, 2016a ), if the corresponding proteins do not interact with each other.…”
Section: Challenge Ii: Obtaining Experimental Data To Set Up the Modelmentioning
confidence: 99%
“…The power of automation is clear in this study, as it was shown that with the same setup it was possible to study the purification of ovalbumin from a mixture with conalbumin and BSA and capture of mAbs. Recently, implementation of a HTS setup coupled to mechanistic modelling showed how data retrieved from MiniColumns can be translated to laboratory‐scale chromatography 60,88,89 . By analyzing the Pe number at different scales, the authors concluded that an increased axial dispersion is observed at smaller scales, compared to larger scales, leading to larger elution pool volumes 60 .…”
Section: Upstream and Downstream Process Development With Htementioning
confidence: 99%
“…Recently, implementation of a HTS setup coupled to mechanistic modelling showed how data retrieved from MiniColumns can be translated to laboratory-scale chromatography. 60,88,89 By analyzing the Pe number at different scales, the authors concluded that an increased axial dispersion is observed at smaller scales, compared to larger scales, leading to larger elution pool volumes. 60 The results then were used to correct the model, allowing for accurate prediction of elution pool volumes at larger scales using the MiniColumns for experimentation.…”
Section: Upstream and Downstream Process Development With Htementioning
confidence: 99%
“…The elution profile is then obtained by plotting the total protein concentration at the exit of the column of length L (∑ p c p (z = L, t)) against the elution volume V elution , i.e. the total volume of the mobile phase that has eluted from the column between t = 0 and time t. Models of this type have been used before in the literature [23,[26][27][28][29][30]. In the present work, v p , ε * p , and k p are considered to be model parameters that depend on the protein p but are otherwise state-independent.…”
Section: Mathematical Model Of the Chromatographic Separationmentioning
confidence: 99%